Gradivo za etnološko kontekstualizacijo muzejskih predmetov kot vir za jezikoslovne raziskave - Ivančič Kutin, Barbara (Jezik in slovstvo, 2017)
The article is a case study intended to demonstrate how the narrative material documented for the ethnological contextualisation of museum objects and collections is also useful for linguistic research, especially for dialectology. An extensive database of spoken language recordings from six western Slovenian dialects and one subdialect, which was acquired in the course of the cross-border project ZborZbirk: Cultural Heritage in the Collections between the Alps and the Karst Region, enables research on all linguistic levels (dialect vocabulary, morphology, syntax). At the text level, it also allows for the aesthetic and stylistic analysis of spoken discourse. Applicability is demonstrated on some concrete examples.
Keywords: muzeji; pripovedke; ustno izročilo; ljudsko slovstvo; oral literature; Slovene dialects; slovenska narečja; besedišče; dialectology; dialektologija